(untitled) (Journal of the College of Basic Education, 2026)
The objective of the current research is to identify the effect of using the developed cluster learning strategy in the pivotal thinking skills of second-grade intermediate students, and to achieve the goal of the research, the researcher adopted the experimental design, if she used the semi-experimental design of two equivalent groups with a post-test to test pivotal thinking skills, the research sample consisted of (69) female students (after excluding failed students) from the second intermediate grade students, the second semester of the academic year (2024-2025), um Al-Qura Intermediate School for Girls was chosen in a way Random, and random selection of the two research groups (experimental and control) was chosen Division (C) to represent the experimental group that was studied according to the strategy of cluster learning developed and by (35) students, and Division (B) to represent the control group that studied according to the usual method and by (34) students, and parity was conducted for the two groups (experimental and control) in the following variables (chronological age in months, knowledge (information) previous in mathematics, intelligence, and previous achievement in mathematics), the research tool was built, namely: Pivotal thinking skills test consists of (30) objective items of the type of multiple choice distributed according to the eight pivotal thinking skills (concentration skill, information collection skill, remembering skill, organization skill, analysis skill, generation skill, integration skill, and evaluation skill) and its branches (21) indicative indicators, and using the equation (kauder-Richardson (KR-20) the value of the stability coefficient was (0.871), and after the completion of the experiment the pivotal thinking skills test was applied to the two research groups (experimental and control) After completing the data collection and analysis using the statistical program (spss_23) for social sciences, the results showed a statistically significant difference at the level of significance (0.05) and in favor of the experimental group in testing pivotal thinking skills. In light of the results of the research, a number of conclusions, recommendations and proposals were reached.